Analisa Economic Balance Pembuatan Alat Jemuran Pakaian Semi-otomatis Dengan Menggunakan Metode Lean Manufacturing - Broto Sasongko, Sukendro; Rivallulloh (P3M Politeknik Negeri Cilacap, 2024)
The analysis of the economic perspective of the cloth hanger semi-automatic by using the lean manufacturing method was studied and analyzed. The economic balance was consider all cost of manufacturing effort. the cost manufacturing of the hanger is to the device, material, cutting, and drilling steps thus assembly. The investigation is to the manufacturing lead time (MLT), and the brake event point (BEP). Production time per unit (TP), the effective work hour per man-hour, the production capacity (PC), and the Payback Period (PBP). The result of economic balances shows are manufacturing lead time (MLT) of 3,38 hours/unit, and BEP (Q) of 1,65 units per month, further, Break break-even point (BEP) is about Rp. 5.345.740,94 per month. So, the profit taking back regards to production capacity is about Rp. 24,672,650,48 per month after selling. The effective work hour of the man-hour is 6 per shift hour per day. Thus, production time reveals 44,92 min per unit. The production capacity per month is to be 8 hours per day and reveals 20 units. The payback period of the clothes hanger will take back after 2 months for more than 2 units sold. That is, the cost of the engine manufacturing will be refunded after 1 month during normal selling.